Evaluating suppliers/consultants and procuring entities in the landscape of public procurement in Bangladesh - Islam, Md. Shahidul (BRAC University, 2015)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.